The Crisis of 1898
IX, 221 p.
Keywords: In 1898 the United States and Spain went to war over the political future of Cuba. At the end of the conflict, the world's distribution of imperial power had dramatically changed, the old Spanish empire giving way to the imperialist ambitions of the young American nation. At the same time, all the countries involved experienced some sort of nationalist mobilisation as a consequence of the war. This book explores the interplay of political, economic, social and military aspects of the 1898 war in the United States, Cuba, Puerto Rico, Spain and the Philippines, all main characters in this short but momentous turn-of-the-century drama.